Domestic and Foreign Institutional Ownership and Sustainable Tax Strategies - Vincentia Evelyn; Clarita Anna Bella; Elisa Tjondro (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2026)
This study aims to explore how institutional domestic and foreign ownership influence sustainable tax strategies (STS) in firms. This research implements Weighted Least Square (WLS) regression as an analytical tool with a final sample of 767 observation for period of 2015 - 2020. There are 158 manufacturing firms listed in Indonesia Stock Exchange (IDX) used as objects in study. Findings in the study show that domestic and foreign ownership structure have impact on STS. This indicated that increases in domestic and foreign ownership within the firms, would lead to a further decrease in the volatility of long-term tax payments. Based on the results of the empirical tests, domestic and foreign ownership were found to influence the enhancement of STS. However, our findings indicated that domestic ownership exhibited a stronger relationship with STS than foreign ownership. This study provided recent evidence that both domestic and foreign ownership within a firm affected the implementation of STS. These findings were expected to imply that firms with higher levels of foreign ownership should be aware of and exercise caution regarding differences in preferences between foreign and domestic owners. Foreign-owned companies are obligated to follow not only domestic tax laws but also foreign tax laws.